2022
DOI: 10.1029/2021gl097367
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Multiple Corona Bursts in Lightning Processes for Radio Frequency Interferometer Observations

Abstract: Recent observations from LOFAR indicate that multiple, spatially distributed corona bursts can occur in lightning processes with a timescale of 10 microseconds. The close proximity of the corona bursts in space and time poses a great observation challenge for short‐baseline (typically ≤100 m) radio interferometers. This paper reports simulations to show the interferometry results that would be obtained with such an interferometer. In particular, spatially‐separated corona bursts at fixed locations may be seen … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…In closing, we comment on the recent study by N. Liu, Scholten, Dwyer, et al. (2022), who showed that short‐baseline, centroid‐detecting INTFs would produce artificially fast propagation speeds between successive pairs of localized sources that are separated both spatially and temporally. This would be due to the sources being spatially unresolved by the short‐baselines of the INTF, and by the centroid of the sources rapidly switching from source A to source B partway between their locations and times of occurrence.…”
Section: Summary and Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In closing, we comment on the recent study by N. Liu, Scholten, Dwyer, et al. (2022), who showed that short‐baseline, centroid‐detecting INTFs would produce artificially fast propagation speeds between successive pairs of localized sources that are separated both spatially and temporally. This would be due to the sources being spatially unresolved by the short‐baselines of the INTF, and by the centroid of the sources rapidly switching from source A to source B partway between their locations and times of occurrence.…”
Section: Summary and Discussionmentioning
confidence: 82%
“…This is due to the VHF radiation during the NBEs being produced by a single localized source that propagates continuously with time, as seen in Figure 1, rather than a pair of discrete sources with intervening lulls in the VHF radiation, as assumed in Figure 2 of N. Liu, Scholten, Dwyer, et al. (2022). More importantly, while the sferics of IBPs are more complex than for NBEs, and exhibit several pairs of impulsive sub‐pulses associated with corona bursts, the received VHF radiation signals have excellent temporal resolution and, like NBEs, show that the VHF radiation is continuously strong and fast during the entirety of the IBPs.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recent studies indicate that the fast breakdowns of NBEs sometimes contain secondary fast breakdowns along the previous path (Attanasio et al, 2021;Rison et al, 2016;Tilles et al, 2019;. Most recent observations from the LOw Frequency ARray (LOFAR) also indicate that multiple, spatially distributed corona bursts can occur in lightning processes with a timescale of 10 µs (N. Liu et al, 2022). The feature of secondary peaks and oscillations might be a fundamental property in NBE radio waveforms (Leal et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies indicate that the fast breakdowns of NBEs sometimes contain secondary fast breakdowns along the previous path (Attanasio et al., 2021; Li, Luque, Gordillo‐Vázquez et al., 2022; Rison et al., 2016; Tilles et al., 2019). Most recent observations from the LOw Frequency ARray (LOFAR) also indicate that multiple, spatially distributed corona bursts can occur in lightning processes with a timescale of 10 µs (N. Liu et al., 2022). The feature of secondary peaks and the microsecond‐scale oscillations might be a fundamental property in NBE radio waveforms (Hamlin et al., 2007; Karunarathne et al., 2015; Leal & Rakov, 2019; Nag & Rakov, 2009).…”
Section: Discussion and Summarymentioning
confidence: 99%